Social Issues in the Family Enterprise. (September 2014) - Van Gils, Anita; Dibrell, Clay; Neubaum, Donald O.; Craig, Justin B.
In this introduction, we discuss social issue research in the management and family business literatures, focusing on ethics, corporate social responsibility, and philanthropic practices of family enterprises. Next, we introduce and highlight four articles accepted for publication. The editorial concludes by presenting future research questions at the social issues—family business interface. Our review of 35 articles, as well as those included in this Special Issue, suggest that family businesses are more attuned and attentive to social issues and stakeholders than nonfamily business. Noneconomic motivations (e.g., reputation, socioemotional wealth, and stewardship) appear particularly salient to family enterprises.